The effects of musical fit on consumers' ability to freely recall related products. - Yeaoh, Joanne P. S.; North, Adrian C. (Ohio State University Library, 2010)
Previous studies have claimed that music can prime the selection of certain products and influence consumers’ propensity to spend because it activates related knowledge of the world and subsequently raises the salience of certain products and behaviours associated with that music. The possibility that music can raise the salience of associated products has not been tested directly, however, and ought to manifest itself through enhanced ability to recall the products in question when associated music is played. Accordingly, this study investigated the impact of musical ‘fit’ on product recall. Participants were asked to list as many Malay and Indian food items as they could while listening to either Malay or Indian music. Among ethnically Chinese participants, more Malay food items were recalled when Malay music was played and more Indian food items were recalled when Indian music was played. Ethnically Malay and Indian participants were more likely to recall food from their own cultures, irrespective of the music played.